Vocalizações e atividade acústica de anuros brasileiros : conhecimento atual, novas descrições e variação temporal em múltiplas escalas. - Batista, Vinicius Guerra (2018)
Acoustic signals of anurans are important mechanisms of reproductive isolation and provide informative characters for identification and delimitation of the species, being used in studies of behavioral, ecology, conservation, taxonomy, biodiversity inventories and influence of environmental impacts on species. In this thesis, we reviewed and measured the knowledge about the advertisement calls of Brazilian anurans, contributing with this knowledge when describing new calls, and also analyzing the temporal variation of the acoustic activity of different species and communities, evaluating the influence of different environmental and social factors. We identified a large knowledge gap regarding call descriptions. Calls of Rhinella abei, Limnomedusa macroglossa e Boana jaguariaivensis were described. Additionally, we evaluated the variation of acoustic parameters in Physalaemus centralis. In relation to the three sympatric Dendropsophus species studied (D. cruzi, D. minutus and D. rubicundulus), there was partition of the acoustic space, as well as of the calling sites. Besides, the Dendropsophus modified their acoustic parameters throughout the night, which may be associated with female preferences or to decrease energetic costs to maintain vocalization activity throughout the reproductive season. At the community level, the anurans presented a circadian pattern, with temporal niche overlap in the acoustic activity during the night, although when evaluated separately the species presented different periods of maximum vocal activity. Climatic variables act as driving factors to determine acoustic activity and the species may use different strategies to avoid overlap in the acoustic niche and facilitate coexistence.